Reclamation of Degraded Land at Regional Level and Conversion of Agricultural Land for Non-Agricultural Purposes - Monika Wasilewicz-Pszczółkowska; Adam Senetra; Agnieszka Szczepańska (Barometr Regionalny)
Intensified anthropogenic pressures contribute to land degradation and devastation around the globe. Land degradation leads to a temporary or a permanent decline in the productive capacity of land. Degraded agricultural land is often converted to non-agricultural uses, as the result areas with natural land cover (arable land, meadows, pastures) are transformed into anthropogenic landscapes. The objective of this study was to analyze the changes in the area of degraded land in the Warmińsko-Mazurskie Voivodship based on the scope of implemented land reclamation measures. The area of land converted for non-agricultural purposes, the revenues generated from conversion fees and their distribution were also evaluated. The analyzed data covered the period of 2007–2012.